Penerapan Dashboard Business Inteligence untuk Bongkar Muat Kapal pada Pelabuhan XYZ Menggunakan Metabase - Arbi Muh’adhim; Prayoga Dwi Supriyadi; Sanjaya Ramadhan; Ma’had Wicaksono (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2025)
The port is a vital infrastructure in the global logistics chain that connects sea and land transportation. The efficiency of cargo loading and unloading operations at the port is a critical factor influencing the smooth flow of goods and overall logistics costs. In this context, the use of Business Intelligence (BI) as an integrated technological system to support data collection, analysis, and presentation is becoming increasingly important for optimizing data-driven decision-making in port environments. XYZ Port, as one of the strategic ports in Indonesia, faces challenges in managing complex loading and unloading operations with increasing cargo volumes. The implementation of a BI dashboard offers a solution to visualize operational data in real-time, identify bottlenecks, and optimize resource allocation. This study aims to implement a BI dashboard for cargo handling operations at XYZ Port. The specific objectives include identifying information needs in cargo handling operations and developing a BI dashboard that suits the characteristics of port operations. The findings indicate that the dashboard effectively supports real-time decision-making and enhances operational efficiency. The study also highlights the importance of addressing technological infrastructure, human resource readiness, and system integration challenges in BI implementation.